A Cooperative Game Theory Model of Quantity Discounts - Kohli, Rajeev; Park, Heungsoo (Management Science, 1989)
Quantity discounts offered by a monopolist are considered in the context of a bargaining problem in which the buyer and the seller negotiate over the order quantity and the average unit price. All-units and incremental quantity discounts that permit transaction at a negotiated outcome are described. The effects of risk sensitivity and bargaining power on quantity discounts are discussed for alternative bargaining models.